Excitatory and Inhibitory Synaptic Imbalance Caused by Brain-Derived Neurotrophic Factor Deficits During Development in a Valproic Acid Mouse Model of Autism - Qi, Chuchu; Chen, Andi; Mao, Honghui; Hu, Erling; Ge, Junye; Ma, Guaiguai; Ren, Keke; Xue, Qian; Wang, Wenting; Wu, Shengxi (Frontiers in Molecular Neuroscience, 2022)
Environmental factors, such as medication during pregnancy, are one of the major causes of autism spectrum disorder (ASD). Valproic acid (VPA) intake during pregnancy has been reported to dramatically elevate autism risk in offspring. Recently, researchers have proposed that VPA exposure could induce excitatory or inhibitory synaptic dysfunction. However, it remains to be determined whether and how alterations in the excitatory/inhibitory (E/I) balance contribute to VPA-induced ASD in a mouse model. In the present study, we explored changes in the E/I balance during different developmental periods in a VPA mouse model. We found that typical markers of pre- and postsynaptic excitatory and inhibitory function involved in E/I balance markedly decreased during development, reflecting difficulties in the development of synaptic plasticity in VPA-exposed mice. The expression of brain-derived neurotrophic factor (BDNF), a neurotrophin that promotes the formation and maturation of glutamatergic and GABAergic synapses during postnatal development, was severely reduced in the VPA-exposed group. Treatment with exogenous BDNF during the critical E/I imbalance period rescued synaptic functions and autism-like behaviors, such as social defects. With these results, we experimentally showed that social dysfunction in the VPA mouse model of autism might be caused by E/I imbalance stemming from BDNF deficits during the developmental stage.